Schwartz-Jampel syndrome in two daughters of first cousins. Issue 2 (February 1978) - Pavone, L; Mollica, F; Grasso, A; Cao, A; Gullotta, F
Abstract : The clinical and pathological features of two sisters born from consanguineous parents and affected by the rare Schwartz-Jampel syndrome are reported. The parental consanguinity of these two patients and the findings of electromyographic changes in the mother strongly support an autosomal recessive pattern of inheritance. No response of growth hormone secretion to arginine and insulin stimulation tests was found.